2012
DOI: 10.5194/hess-16-3075-2012
|View full text |Cite
|
Sign up to set email alerts
|

Physical models for classroom teaching in hydrology

Abstract: Abstract. Hydrology teaching benefits from the fact that many important processes can be illustrated and explained with simple physical models. A set of mobile physical models has been developed and used during many years of lecturing at basic university level teaching in hydrology. One model, with which many phenomena can be demonstrated, consists of a 1.0-m-long plexiglass container containing an about 0.25-m-deep open sand aquifer through which water is circulated. The model can be used for showing the grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…The introduction of learnercentered demonstrations, such as small experiments conducted with Darcy bottles or a plexiglass tank, to illustrate concepts associated to groundwater flow into lecture classes is reported to trigger sophisticated questions and discussions. Physical models may help to address quantitative aspects (such as order of magnitude of groundwater fluxes or hydrodynamic parameters) of hydrogeology education (Neupauer and Dennis, 2010;Rodhe, 2012). Numerical models may help to assess and visualize the influence of the parameters involved in hydrogeological processes such as velocity and concentration fields (Singha and Loheide II, 2011) or to address basic modeling concepts such as sensitivity…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of learnercentered demonstrations, such as small experiments conducted with Darcy bottles or a plexiglass tank, to illustrate concepts associated to groundwater flow into lecture classes is reported to trigger sophisticated questions and discussions. Physical models may help to address quantitative aspects (such as order of magnitude of groundwater fluxes or hydrodynamic parameters) of hydrogeology education (Neupauer and Dennis, 2010;Rodhe, 2012). Numerical models may help to assess and visualize the influence of the parameters involved in hydrogeological processes such as velocity and concentration fields (Singha and Loheide II, 2011) or to address basic modeling concepts such as sensitivity…”
Section: Introductionmentioning
confidence: 99%
“…The value of field research for enhancing scientific understanding in hydrology is undisputed and has been demonstrated through a wide range of educational studies (Carlson, 1999;de Wet, 1994;Dunnivant et al, 1999;Hudak, 1999;Trop et al, 2000), but decreasing funding and increasing student numbers have further reduced the availability of hands-on experience during undergraduate education at many universities. How to deal with this issue remains an unsolved problem (though see ideas of Rodhe, 2012). Our own work has focused on advancing the other four points though, and we will concentrate the rest of the paper on them.…”
Section: Opportunities Through Open Educationmentioning
confidence: 99%
“…Studies have for example assessed the value of computing in conveying concepts of data analysis or modeling in hydrology (Elshorbagy, 2005;Hossain and Huddleston, 2007;Wagener and McIntyre, 2007;Schwenk et al, 2009;Aghakouchak and Emad, 2010), which is less straightforward than it might appear (Whiteman and Nygren, 2000). Others have attempted to use watersheds as an integration scale outside hydrology (Salvage et al, 2004), or tested how the use of physical model can reduce misperceptions of hydrological processes (see references in Rodhe, 2012). In addition to the increasing societal recognition of water-related issues and threats, there are opportunities to enhance hydrology education by linking it to popular concepts such as sustainability or millennium development goals, e.g., access to clean water (Mihelcic et al, 2008) or risk in regard to natural hazards (Boynton and Hossain, 2010).…”
Section: Hydrology Education Assessmentmentioning
confidence: 99%
“…Pri Naravoslovju in tehniki v 5. razredu jim razložijo vodni krog in kaj so podzemna voda, pitna voda, onesnaženje vode, vodne zaloge in oskrba z vodo ter fizikalne lastnosti tal (voDoPivec et al, 2011). Pri Naravoslovju v 7. razredu spoznavajo vodo kot kemi~no spojino (Skvar~ et al, 2011). Pri Kemiji v 8. in 9. razredu sli�ijo o podzemni vodi kot raztopini in povzro~iteljici kra�kih pojavov (Ba~nik et al, 2011).…”
unclassified